NIMG-78. EVALUATION OF ISCHEMIC COMPLICATIONS IN REMOVAL OF GLIAL TUMOR. (5th November 2018) - Higuchi, Tadashi; Yamaguchi, Fumiio; Oomura, Tomoko; Sato, Shun; Adachi, Koji; Morita, Akio
Abstract: INTRODUCTION: Recently, the use of navigation system, brain mapping, and intraoperative photo diagnosis during tumor resection becomes possible to prevent maximally neurological function and undergo surgery safety. However, postoperative ischemic complication is unpredictability, as a result, it may cause neurological deficits. We examined retrospectively how predicted ischemic complication and intraoperative important point to avoid complication. METHODS: In our institute, 45 glioma patients underwent tumor resection using neuro-navigation system, brain mapping, and 5-ALA PD from 2013 to 2017. Evaluation of presence or absence of postoperative ischemic complication was measuring distance between removal cavity and ischemia lesion, referring diffusion-weighted MR image. And, evaluation of presence or absence of neurological deficits were referred to medical records. RESULTS: In all 45 cases, 30 cases (68%) appeared abnormal change in diffusion-weighted MR image, 7 cases (17%) of them had neurological deficits because of ischemic complication. All cases of within 5mm ischemic complication from removal cavity with MRI had not clinical neurological deficits. CONCLUSION: More than half our cases appeared ischemic complication. And it is considered necessary to undergo operation while thinking possibility of onset risk of ischemic complication. In particular, resection of brain tumor near eloquent area, we suggest one method of residual tumor 5mm from eloquent area because of prevent neurological function.